Association between age, urine pH, and urinary stone incidence in Kardinah Tegal General Hospital, Indonesia - Zulfikar Ali; Stevano Lucianto Hotasi (Intisari Sains Medis, 2020)
Introduction: An increase in the incidence of urolithiasis at age> 15 years in Indonesia provides increased morbidity and medical costs. The study aims to determine the association between age, urine pH, and urinary stones incidence in Kardinah Tegal General Hospital, Indonesia.Method: There were 240 subjects from July to August 2019, with urolithiasis in Kardinah Tegal General Hospital who never received any previous treatment for urolithiasis. Subjects were divided into 120 subjects in case group and 120 subjects in control group. Medical records were assessed and reviewed for age, gender, urinalysis (including urine pH), urinary tract infection (UTI), and urinary stones incidence. Kolmogorov-Smirnov was used to assess data distribution of age and urine pH, and Chi-square test was used to evaluate the association between each age category and urinary pH.Results: Subject’s mean age between urolithiasis and non-urolithiasis groups were 47.68 ± 11.74 and 55.49 ± 15.72 years old, respectively There are no significant differences in stone incidence according to urinary pH in both groups. Stone incidence was found to be highest in age group of 50-59 years old in acidic urinary pH. No age group and urinary pH were associated with stone incidence. The odds of urinary stones occurrence would be 0.689 times more likely to happen with the increase of urinary pH,Conclusion: There was significant difference of age between urolithiasis and non-urolithiasis groups. No age group and urinary pH were found associated with stone incidence, however the increase of age and urinary pH, increase the odds of developing urinary stones.